1995
DOI: 10.2307/2410406
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Origin of a Parthenoform, The Amazon Molly Poecilia formosa, on the Basis of a Molecular Genealogy

Abstract: The appearance of vertebrate species that reproduce without genetic recombination has been explained by their origin from a rare hybridization event between members of two distantly related species. For the first recognized vertebrate unisexual, the Amazon molly Poeciliaformosa, mostly morphological and biochemical genetic information has been available so far with respect to its evolutionary origin. DNA sequence analyses of transcribed portions of the genome (tyrosine kinase proto-oncogenes) demonstrated its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 8 publications
5
141
0
Order By: Relevance
“…Similar results were found in parthenogenetic geckos (Moritz & Heideman 1993;Kearney et al 2006). Recent analyses that included information from mitochondrial as well as nuclear DNA suggested that the initial hybridization event leading to the formation of P. formosa happened ca 280 000 years ago (Schartl et al 1995b;Meyer et al 2006). Estimating three generations per year (Hubbs & Hubbs 1932), this equals approximately 840 000 generations.…”
Section: Interspecific Hybridization Leading To the Origin Of The Amasupporting
confidence: 69%
See 2 more Smart Citations
“…Similar results were found in parthenogenetic geckos (Moritz & Heideman 1993;Kearney et al 2006). Recent analyses that included information from mitochondrial as well as nuclear DNA suggested that the initial hybridization event leading to the formation of P. formosa happened ca 280 000 years ago (Schartl et al 1995b;Meyer et al 2006). Estimating three generations per year (Hubbs & Hubbs 1932), this equals approximately 840 000 generations.…”
Section: Interspecific Hybridization Leading To the Origin Of The Amasupporting
confidence: 69%
“…Mitochondrial DNA showed that P. mexicana was the female parent of P. formosa (Avise et al 1991). Sequence analyses of nuclear genes and a phylogenetic analysis suggested a subspecies of P. mexicana, Poecilia mexicana limantouri to be the maternal ancestor of P. formosa (Turner et al 1980a;Schartl et al 1995b). Molecular evidence for the hybrid origin of P. formosa was also found with serum samples and later confirmed by allozyme data (Turner et al 1980b).…”
Section: Interspecific Hybridization Leading To the Origin Of The Amamentioning
confidence: 77%
See 1 more Smart Citation
“…The DNA probe used in Southern hybridization experiments is a 647-bp XbaI-XhoI subfragment of the original EcoRI fragment containing only the partial Poseidon element. Genomic DNA was isolated as described (Schartl et al 1996). For Southern analysis, genomic DNA was blotted, after EcoRI digestion and electrophretic fractionation, onto positively charged nylon membranes and hybridized with the probe at 42°C in 35% formamide, 0.1% sodium pyrophosphate, 50 mM TRIS-HCl (pH 7.5), 5´SSC, 1% SDS, 5´Denhardt's solution, and 100 lg/ml calf thymus DNA.…”
Section: Dna Manipulationsmentioning
confidence: 99%
“…Sexually antagonistic coevolution is typically thought of as an intraspecific process, but mating interactions between species can also generate interspecific conflict between the sexes that in some cases may impose even stronger selective pressures than those acting intraspecifically [7,8]. The costs and benefits of hybridization can vary in magnitude and even direction between species and sexes [9][10][11], with the same hybrid progeny representing a fitness benefit for one parent but a cost to the other.…”
Section: Introductionmentioning
confidence: 99%